Investigating the coupling of narrative and locality in augmented reality educational activities: Effects on students’ immersion and learning gains - Georgiou, Yiannis; Kyza, Eleni A. (My University, 2018)
The popularity of Augmented Reality (AR) technologies is on the rise, yet little is known about the design principles which could support immersion and learning in such contexts. This study investigated the hypothesis that greater coupling between the physical space and the narrative of the AR activity leads to enhanced immersion and learning. Forty-five middle school students participated in this study: students in Condition1 (n=22) participated in an AR activity with strong coupling between the narrative and the physical space, while students in Condition2 (n=23) participated in a loose coupling version of the activity. Data collection included baseline data, questionnaires investigating students’ immersion and learning gains, as well as post-activity interviews. Findings showed higher learning gains and increased immersion for the students participating in the strong coupling condition than for the students in the loose coupling condition.
Keywords: Augmented reality; Students; Educational activities; Higher learning